Effect of mixing pigs or maintaining pen integrity on the response to growing-finishing space allocation - M C Brumm; L J Johnston; K Stalder; NCERA-89 Committee on Swine Mangement; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 2006)
A cooperative study using 906 pigs was conducted to evaluate either mixing pigs or maintaining pen integrity during the move from nursery to finishing, and its effect on finishing space allowance. Treatments were arranged in a 2 × 2 factorial, with main effects of mixing or maintaining pen integrity as pigs were moved to finishing facilities (BW 54.9 lb) and providing either 6.0 or 8.0 ft2 per pig. There were 8 pens per block and 7 blocks. In 2 pens, when moving from nursery to finishing, pen integrity was maintained and pens were allocated either 6.0 or 8.0 ft2 per pig. For mixed treatments, pigs from 3 pens were mixed into 3 new pens and were assigned 6.0 ft2 per pig. Likewise, 3 more pens were mixed and were assigned 8.0 ft2 per pig. Individual pen was the experimental unit. From d 0 to 14, no treatment effects were observed (P>0.16). A mixing by space allocation interaction was observed (P<0.05) for overall ADG and F/G. The interactions were a result of mixed pigs at 6.0 ft2 having better ADG and F/G than unmixed pigs, whereas unmixed pigs had better ADG and F/G at 8.0 ft2. Despite the interactions, the actual differences between treatment groups were relatively small. Overall (d 0 to 118), maintaining pen integrity did not affect ADG or ADFI, compared with mixing pigs (1.92 and 5.20 vs. 1.93 and 5.20 lb/d, respectively). But pigs provided 6.0 ft2 had decreased ADG (P<0.01) and ADFI (P<0.01), compared with those of pigs provided 8.0 ft2 (1.90 and 5.16 vs. 1.95 and 5.25 lb/d, respectively). These results confirm expected reductions in growth and feed intake of pigs restricted in space. In this study, maintaining pen integrity when moving pigs from nursery to finishing facilities had no beneficial effect on pig performance, compared with mixing pigs into new social groups.; Swine Day, 2006, Kansas State University, Manhattan, KS, 2006
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-83-S; Swine day; 2006; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 966; Mixing; Pigs; Space; Swine